Evaluation of Science Communication: Current Practices, Challenges, and Future Implications - Ziegler, Ricarda; Hedder, Imke Ronja; Fischer, Liliann (Frontiers in Communication, 2021)
Scientifically substantiated evaluations are pivotal for ensuring the effectiveness and improvement of the growing number of science communication projects. Yet, current evaluation practices are still lacking in various respects. Based on a systematic review of evaluation reports, an online survey of as well as discussion rounds with science communication practitioners in the German-speaking countries, we discuss three main challenges to science communication evaluation: (1) There is a conflation of impact goals and measurable project objectives as well as a lack of precise definitions of objectives and target groups, which complicates the assessment of the projects’ success. (2) Although many evaluations highlight the impact-oriented interest of those responsible, the methods chosen rarely allow scientifically valid evaluations of effects. The lack of comparative reference points and the partially unsuitable use of self-report measures are key issues in this regard. (3) The fact that few evaluation processes are made transparent and that formative evaluation designs are a rarity, indicate a tendency to understand evaluations as the final “success story” of a project rather than a learning process. This stands in the way of a constructive discussion of the actual impact of science communication. Our exploratory insights contribute to an understanding of the weaknesses of science communication evaluation and needs in the field. They also provide impulses for future improvements in the field for stakeholders in practice, research, funding and science management.